2018
DOI: 10.1007/s11262-018-1603-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Pteropine orthoreovirus from Pteropus vampyrus in Garut, Indonesia

Abstract: Flying foxes belonging to the genus Pteropus are known to be reservoirs of zoonotic viruses. In this study, we describe the isolation of Pteropine orthoreovirus (PRV) from rectal swab samples of Pteropus vampyrus in Indonesia. PRV is an emerging zoonotic respiratory virus that can be transmitted from bats to humans. Rectal swabs (n = 91) were screened by PCR for PRV and 10 (11%) were positive. Phylogenetic analysis based on nucleotide sequences indicated that the S2, S3, S4, M3, L2, and L3 segments of one isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…It is important to note that, almost in all of the cases, an intermediate host has been identified to play a crucial role in amplifying and transmitting the virus from bats to humans such as horses for Hendra virus, pigs for Nipah virus and palm civets for SARS-CoV [25][26][27][28][29]. With multiple reports of PRV presence in bats in many parts of Asia [2,12,[14][15][16][17] and a higher than expected prevalence in certain human populations [7][8][9], we raised the hypothesis that it is possible that a yet-to-be-identified intermediate host(s) may also play a role in the spillover of PRVs from bats to humans. Alternatively, an additional reservoir may play a role in zoonotic transmission of PRV, as is the case with camels and MERS-CoV [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that, almost in all of the cases, an intermediate host has been identified to play a crucial role in amplifying and transmitting the virus from bats to humans such as horses for Hendra virus, pigs for Nipah virus and palm civets for SARS-CoV [25][26][27][28][29]. With multiple reports of PRV presence in bats in many parts of Asia [2,12,[14][15][16][17] and a higher than expected prevalence in certain human populations [7][8][9], we raised the hypothesis that it is possible that a yet-to-be-identified intermediate host(s) may also play a role in the spillover of PRVs from bats to humans. Alternatively, an additional reservoir may play a role in zoonotic transmission of PRV, as is the case with camels and MERS-CoV [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been at least 15 different accounts identifying PRVs from either human outbreak investigations or bat virome studies [1][2][3][4]6,[10][11][12][13][14][15][16][17]. It is well known that interspecies transmission of bat-borne viruses is a source of disease outbreaks in the human population and indeed evidence of bat-to- human transmission of PRV has been demonstrated [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…The genome of PRV consists of 10 segments divided into three size classes based on gel electrophoresis mobility shift characteristics, namely, three large segments (L1-L3), three medium segments (M1-M3), and four small segments (S1-S4) [11]. To date, 15 PRV strains have been isolated from six fruit bat species (Pteropus poliocephalus, Pteropus hypomelanus, Pteropus vampyrus, Rousettus leschenaultia, Rousettus amplexicaudatus, and Eonycteris spelaea) in Australia, Malaysia, Indonesia, China, and the Philippines (S1 Table) [1,[12][13][14][15][16][17]. Serological study of PRV in the Philippines reported that 83% of the tested bats (70/ 84) had neutralizing antibodies to PRV, suggesting that PRV is a common infection in wild bat populations in Southeast Asia [16].…”
Section: Introductionmentioning
confidence: 99%
“…The first PRV to be isolated, Nelson Bay orthoreovirus (NBV; previously known as Nelson Bay virus), was isolated from the gray-headed flying fox (Pteropus poliocephalus) in Australia in 1968 [10]. Since then, PRVs have been isolated from some frugivorous and nectarivorous bats in Malaysia, Indonesia, Philippines, and China [11][12][13][14]. Viral transmission from bats to humans occurs in these regions, as revealed by viral isolation from people living near bat roosts in Malaysia and by serological studies conducted in Malaysia, Vietnam, and Singapore [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%